2016
DOI: 10.1155/2016/3837679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Osseointegration by Bone Morphogenetic Protein-2 on Titanium Implants In Vitro and In Vivo

Abstract: This study designed a biomimetic implant for reducing healing time and achieving early osseointegration to create an active surface. Bone morphogenetic protein-2 (BMP-2) is a strong regulator protein in osteogenic pathways. Due to hardly maintaining BMP-2 biological function and specificity, BMP-2 efficient delivery on implant surfaces is the main challenge for the clinic application. In this study, a novel method for synthesizing functionalized silane film for superior modification with BMP-2 on titanium surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…rh‐bone morphogenetic protein‐2 is contraindicated in patients allergic to collagen, patients who are pregnant, have an infection in or near the recipient site, had or currently have a tumor in the area of the graft, are skeletally immature (adolescent), or have an arteriovascular malformation . Growth factors can be used to promote vascularization, stem cell recruitment, and to improve the rate of healing of the surgical site, thereby reducing the duration of treatment as well as the amount of graft material needed; they may also cause adverse events and complications such as immune responses, inflammation, ectopic bone formation, infection, osteolysis at the area of delivery, an inordinate amount of edema, adipogenesis, and bone cyst. Other complications associated with the use of rh‐bone morphogenetic protein‐2 include root resorption and ankylosis of adjacent teeth, as well as oral erythema, mouth pain, and ecchymosis .…”
Section: Risks Of New Technologiesmentioning
confidence: 99%
“…rh‐bone morphogenetic protein‐2 is contraindicated in patients allergic to collagen, patients who are pregnant, have an infection in or near the recipient site, had or currently have a tumor in the area of the graft, are skeletally immature (adolescent), or have an arteriovascular malformation . Growth factors can be used to promote vascularization, stem cell recruitment, and to improve the rate of healing of the surgical site, thereby reducing the duration of treatment as well as the amount of graft material needed; they may also cause adverse events and complications such as immune responses, inflammation, ectopic bone formation, infection, osteolysis at the area of delivery, an inordinate amount of edema, adipogenesis, and bone cyst. Other complications associated with the use of rh‐bone morphogenetic protein‐2 include root resorption and ankylosis of adjacent teeth, as well as oral erythema, mouth pain, and ecchymosis .…”
Section: Risks Of New Technologiesmentioning
confidence: 99%
“…[12][13][14] In particular, recombinant human bone morphogenetic protein-2 (rhBMP-2) is a well-known bioactive molecule and a powerful inducer of early differentiation events in mesenchyme stem cells leading to bone formation. 15,16 Therefore, for decades, many researchers have continued to apply rhBMP-2 on the surface of dental implants through various surface modification techniques. [16][17][18] For maximizing clinical effectiveness in biomolecule treatment, the application of a biocompatible polymer to the implant surface assists in stably loading a specific amount of rhBMP-2 onto the implant.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Therefore, for decades, many researchers have continued to apply rhBMP-2 on the surface of dental implants through various surface modification techniques. [16][17][18] For maximizing clinical effectiveness in biomolecule treatment, the application of a biocompatible polymer to the implant surface assists in stably loading a specific amount of rhBMP-2 onto the implant. Several studies have examined the polymer coating layer as a versatile carrier for controlling the release rate and duration of incorporated BMPs through modification of its structures.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that cellular interaction with materials is cell type specific. 41,42 It has even been reported that ECs show a cell origin dependent responsiveness to substrates. 43 To investigate if primary cells are more sensitive to structured fibers, HUVECs from a source of pooled isolated primary cells were cultured on MF or structured MF membranes (Fig.…”
Section: Discussionmentioning
confidence: 99%